Importowane naczynie brązowe ze stemplem Publiusza Cipiusza Polibiusza na cmentarzysku kurhanowym z okresu wpływów rzymskich w Grudnej, pow. złotowski, stan. 2 - Kołoszuk, Igor (Folia Praehistorica Posnaniensia, 2015)
During excavations at the Roman Iron Age barrow cemetery in Grudna there has been an imported skillet discovered with a stamp of Publius Cipius Polybius, a bronzesmith of Capua. It is one of several such vessels found in northern Barbaricum. The largest concentration of skillets has been observed on Danish islands, which at the time were a transit points on a northern trade route across the sea. The presence of the skillet in the area proves widespread, interregional contacts of people inhabiting the middle Gwda River basin in phase B2 of the Roman Iron Age.